A COMPARISON OF MATHEMATICS LEARNING INTEREST OF FIFTH-GRADE STUDENTS AT SDN 30 PEKANBARU AND SDN 188 PEKANBARU - Joesfhinto Prasetio; Syahrilfuddin Syahrilfuddin; Eddy Noviana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research was initiated by several internal factors influencing the learning outcomes, namely learning interest. Learning interest is highly related to students’ learning outcomes. The indicators of learning interest are feeling happy, interested, accepting, and students’ involvement. This purposes of this study were to determine the learning interest of fifth-grade students at SDN 30 Pekanbaru and SDN 188 Pekanbaru and to find out the differences in mathematics learning interests of fifth-grade students at SDN 30 Pekanbaru and SDN 188 Pekanbaru. The type of this research was descriptive quantitative research. The population in this study were all fifth-grade students at SDN 30 Pekanbaru and SDN 188 Pekanbaru. The samples in this study were selected through purposive sampling. The results found that the mathematics learning interest of fifth-grade students at SDN 30 Pekanbaru was categorized as very interested with a percentage of 78.49% and similarly, the mathematics learning interest of fifth-grade students at SDN 188 Pekanbaru was also classified into very interested with a percentage of 83.36%. This research also revealed that there were differences in the mathematics learning interest between fifth-grade students at SDN 30 Pekanbaru and SDN 188 Pekanbaru.